Melatonin-induced DNA demethylation of metal transporters and antioxidant genes alleviates lead stress in radish plants. (1st June 2021) - Tang, Mingjia; Xu, Liang; Wang, Yan; Dong, Junhui; Zhang, Xiaoli; Wang, Kai; Ying, Jiali; Li, Cui; Liu, Liwang
Abstract: Melatonin (MT) is a tryptophan-derived natural product that plays a vital role in plant response to abiotic stresses, including heavy metals (HMs). However, it remains elusive how exogenous MT mediates lead (Pb) accumulation and detoxification at the methylation and transcriptional levels in radish. In this study, decreased Pb accumulation and increased antioxidant enzyme activity were detected under MT treatment in radish. Single-base resolution maps of DNA methylation under Pb stress (Pb200) and Pb plus MT treatment (Pb_50MT) were first generated. The genome-wide methylation level was increased under Pb stress, while an overall loss of DNA methylation was observed under MT treatment. The differentially methylated region (DMR)-associated genes between Pb_50MT and Pb200 were uniquely enriched in ion binding terms, including cation binding, iron ion binding, and transition metal ion binding. Hyper-DMRs between Pb200 and Control exhibited a decreasing trend of methylation under Pb_50MT treatment. A few critical upregulated antioxidant genes (e.g., RsAPX2, RsPOD52 and RsGST ) exhibited decreased methylation levels under MT treatment, which enabled the radish plants to scavenge lead-induced reactive oxygen species (ROS) and decrease oxidative stress. Notably, several MT-induced HM transporter genes with low methylation (e.g., RsABCF5, RsYSL7 and RsHMT ) and transcription factors (e.g., RsWRKY41 and RsMYB2 ) were involved in reducing Pb accumulation in radish roots. These findings could facilitate comprehensive elucidation of the molecular mechanism underlying MT-mediated Pb accumulation and detoxification in radish and other root vegetable crops.